Similarities and differences in the structures and proteoform profiles of the complement proteins C6 and C7 - Lukassen, Marie V; Franc, Vojtech; Hevler, Johannes F; Heck, Albert J R (Wiley, 2021)
The human complement system provides a first line of defence against pathogens. It requires a well-orchestrated sequential assembly of an array of terminal complement components (C5, C6, C7, C8, and C9), ultimately forming the membrane attack complex (MAC). Although much information about MAC assembly is available, the structure of the soluble C7 has remained elusive. The complement proteins C7 and C6 share very high sequence homology and exhibit several conserved domains, disulphide bridges, and C-mannosylation sites. Here, we used an integrative structural MS-based approach combining native MS, glycopeptide-centric MS, in-gel cross-linking MS (IGX-MS) and structural modelling to describe structural features, including glycosylation, of human serum soluble C7. We compare this data with structural and glycosylation data for human serum C6. The new structural model for C7 shows that it adopts a compact conformation in solution. Although C6 and C7 share many similarities, our data reveals distinct O-, and N-linked glycosylation patterns in terms of location and glycan composition. Cumulatively, our data provide valuable new insight into the structure and proteoforms of C7, solving an essential piece of the puzzle in our understanding of MAC assembly.
Keywords: complement; cross-linking; glycosylation; mass spectrometry; proteoforms; Biochemistry; Molecular Biology